Compagnia di giro. La transizione dei chimici italiani dal fascismo alla democrazia - Cerruti, Luigi (Chimica nella Scuola, 2022)
The leading group of the Italian chemical community passed from the fascist regime to the post-war democracy without any upheaval. Also, the chemists, who were most heavily involved in the fascist policy, were not seriously hit by the tribunals which had to judge them or escaped any trial. The transition took place amid total academic solidarity.